Calreticulin inhibits commitment to adipocyte differentiation - Szabo, Eva (The Rockefeller University Press, 2008)
Calreticulin, an endoplasmic reticulum (ER) resident protein, affects many critical cellular functions, including protein folding and calcium homeostasis. Using embryonic stem cells and 3T3-L1 preadipocytes, we show that calreticulin modulates adipogenesis. We find that calreticulin-deficient cells show increased potency for adipogenesis when compared with wild-type or calreticulin-overexpressing cells. In the highly adipogenic crt(−/−) cells, the ER lumenal calcium concentration was reduced. Increasing the ER lumenal calcium concentration led to a decrease in adipogenesis. In calreticulin-deficient cells, the calmodulin–Ca(2+)/calmodulin-dependent protein kinase II (CaMKII) pathway was up-regulated, and inhibition of CaMKII reduced adipogenesis. Calreticulin inhibits adipogenesis via a negative feedback mechanism whereby the expression of calreticulin is initially up-regulated by peroxisome proliferator–activated receptor γ (PPARγ). This abundance of calreticulin subsequently negatively regulates the expression of PPARγ, lipoprotein lipase, CCAAT enhancer–binding protein α, and aP2. Thus, calreticulin appears to function as a Ca(2+)-dependent molecular switch that regulates commitment to adipocyte differentiation by preventing the expression and transcriptional activation of critical proadipogenic transcription factors.